1996
DOI: 10.1111/j.1365-2621.1996.tb10981.x
|View full text |Cite
|
Sign up to set email alerts
|

Thawing, Refreezing and Frozen Storage Effects on Muscle Functionality and Sensory Attributes of Frozen Cod (Gadus morhua)

Abstract: Thawing and re-freezing of cod fillet blocks did not necessarily result in greater deterioration (relative to a 'once frozen' control) of cooked fish sensory attributes after 9 months frozen storage at Ϫ22ЊC. Thawed and refrozen fish muscle displayed a faster decline in myofibril protein solubility than once frozen controls and had reduced water-holding capacity but analysis of proton spin-spin relaxation times indicated no change in water location. The decline in protein solubility was not caused by complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
3
25
2
Order By: Relevance
“…We could recognise, in general, a clear difference in colour between SF and DF samples [29]. It should be mentioned that the effect of double freezing on colour, as discussed above, is not comparable with results reported recently [10] where an increase in the grey appearance of double frozen cooked cod fillets was mentioned especially after very slow thawing before refreezing. There are a number of reports available on colour changes due to freezing.…”
Section: Colour Measurementcontrasting
confidence: 38%
See 1 more Smart Citation
“…We could recognise, in general, a clear difference in colour between SF and DF samples [29]. It should be mentioned that the effect of double freezing on colour, as discussed above, is not comparable with results reported recently [10] where an increase in the grey appearance of double frozen cooked cod fillets was mentioned especially after very slow thawing before refreezing. There are a number of reports available on colour changes due to freezing.…”
Section: Colour Measurementcontrasting
confidence: 38%
“…However, it was not possible to distinguish between single and double frozen fillets after frozen storage of nine months since no significant differences in the sensory quality parameters could be detected. Refrozen cod fillets also showed a loss of protein solubility and a decreased water-binding ability [10]. Further, the observation of physico-chemical changes of cod muscle proteins which were subjected to different freeze-thaw cycles revealed a significant decrease in protein solubility as the freeze-thaw cycles were increased [11].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, it was reported that progressive increase in the hardness of chilled salted catfish (Yashoda and Rao, 1998), mackerel meat (Shimomura and Matsumoto, 1985) and salmon fillets g up to 70 g). Earlier reports using fresh species like cod, haddock, hake, Alaska pollock, and tilapia but to a lesser extent with salmon or trout (Gill et al, 1979;Hurling and McArthur, 1996;Kreuger and Fennema, 1989) have shown that protein denaturation, water loss and toughening of fresh fish are associated with frozen storage. This has mainly been attributed to conformational transitions of muscle proteins, mainly actin and myosin, that lead to protein aggregation, involving hydrophobic interactions, hydrogen bridges and the formation of covalent, non-disulphide bonds as well as to changes in the structure of the water, and/or alterations in the protein-water interactions; together with a transfer of water to larger spatial domains (Del Mazo et al, 1999;Tejada, 2001;Herrero et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding T 22 mean values in these studies were 306, 117, and 122-224 ms. Moreover, Hurling and McArthur (1996) demonstrated that T 2 relaxation times of cod, stored at -70 and -22°C, subjected to either slow or fast thawing and re-freezing, showed no clear changes in the amount of what they referred to as "free water" (T 22 ). Moreover, all treatments exhibited similar patterns of water distribution, even after 9 months of frozen storage.…”
Section: Nmr Proton Relaxation Behaviormentioning
confidence: 99%